A case for trans-local police governance - Houtsonen, Jarmo (European journal of criminology, 2019)
We argue that in the present conditions of differentiated societies a preferable form of police governance and accountability should both be built upon and actively strive towards universal and trans-local criteria, rather than be built upon on some local features or idiosyncrasies. The local governance of the police appears too simple a remedy for police legitimacy and accountability since it might predispose the police to unprofessionalism and heterogeneity of standards, making it vulnerable to co-optation by powerful local interests. The article is based on our experiences of the Finnish form of police governance that has functioned quite well, partly because policing is embedded in the Nordic welfare state model, which strongly supports citizens’ universal rights and social equality. However, the ideas put forward are urgently needed in differentiated societies, characterized by increasing socioeconomic inequality and multiple sources of cultural identity and belongingness. For us the concept of spatial representation appears to be a fundamental aspect in all governance. The argument rests on the idea that modern, differentiated society calls for representations of spatiality and belongingness that are inclusive rather than exclusive, universal rather than particular and trans-local rather than local. Our arguments for trans-local police governance are specified in terms of the universal rule of law, a uniform approach to policing, general professional police competencies and a general professional ethos in policing.